The Impact of Community Housing Characteristics and Epidemic Prevention Measures on Residents’ Perception of Epidemic Prevention - Kuo, Chi-Tz (Int J Environ Res Public Health, 2021)
Since the outbreak of COVID-19, many parts of the world have fallen into deep recession. Governments in every country have adopted various measures to restrict social gatherings due to the need to control the pandemic. This includes restrictions on activities in homes and communities. Fundamentally, epidemic prevention relies on the measures individuals take. A community’s epidemic prevention measures become more critical as activities are held in houses or communities once again. From the perspective of the theory of planned behavior, this study investigates whether the various epidemic prevention measures and characteristics of a community affect residents’ perception of epidemic prevention. We use the truncated regression model as the primary research method. The empirical results show that the community’s epidemic prevention measures can change residents’ awareness of the importance of epidemic prevention. Moreover, the scale of the community and management committee are also found to have a partial impact.